Concomitant congenital heart defect repair and Nuss procedure for pectus excavatum. (February 2014) - Kandakure, Pramod Reddy; Dhannapuneni, Ram; Venugopal, Prem; Franks, Roger; Alphonso, Nelson
The combination of complex congenital cardiac anomalies and pectus excavatum represents a technical challenge. Most concomitant repairs have been performed in adult patients. We report the uncomplicated concomitant repair of double-outlet right ventricle with absent pulmonary valve syndrome and the Nuss procedure for pectus excavatum in a 3-year-old child.